2015
DOI: 10.1111/jeu.12201
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Response of the Toxic Dinoflagellate Karenia mikimotoi Against Grazing by Three Species of Zooplankton

Abstract: We investigated the toxicity of Karenia mikimotoi toward three model grazers, the cladoceran Moina mongolica, the copepod Pseudodiaptomus annandalei, and the crustacean Artemia salina, and explored its chemical response upon zooplankton grazing. An induction experiment, where K. mikimotoi was exposed to grazers or waterborne cues from the mixed cultures revealed that K. mikimotoi might be toxic or nutritionally inadequate toward the three grazers. In general, direct exposure to the three grazers induced the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…Selander et al found that waterborne cues from grazing copepods could increase the cell-specific paralytic shellfish poisoning (PSP) toxin [45]. Dang et al reported that some grazers could increase the toxicity of K. mikimotoi [44]. Here, we found that OA production in P. lima was significantly increased in the presence of A. salina , suggesting the possible anti-grazing role of OA.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Selander et al found that waterborne cues from grazing copepods could increase the cell-specific paralytic shellfish poisoning (PSP) toxin [45]. Dang et al reported that some grazers could increase the toxicity of K. mikimotoi [44]. Here, we found that OA production in P. lima was significantly increased in the presence of A. salina , suggesting the possible anti-grazing role of OA.…”
Section: Discussionsupporting
confidence: 51%
“…It has been found that some phycotoxins can function as inducible defensive chemicals against grazing or reducing the number of grazers to ensure that they were not cleared by grazers [44,56,57]. Nowadays, numerous studies have shown that this inducible reaction is common in phytoplankton, which can reduce the grazing pressure to maintain the survival of the population [57,58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These other substances include hemolytic and cytotoxic compounds gymnocin A and B in addition to a mixture of liposaccharides and lipids [ 33 , 167 , 168 , 169 ]. K. mikimotoi and K. papilionacea produces ichtiotoxic polyunsaturated fatty acids (PUFA), such as eicosapentaenoic acid, and hemolytic toxins that decrease the survival rate of the grazers [ 170 , 171 , 172 ]. The PUFA produced by K. mikimotoi were toxic for various tissue cultures, decreased bacterial bioluminescence and were allelopathic to various algae as it disrupted their cell membranes [ 173 , 174 ] (see also [ 66 ] for review).…”
Section: Compounds Produced By Karenia and Their Physiological Efmentioning
confidence: 99%
“…Toxins produced by K. mikimotoi have ecological implications for marine organisms, although these have not been quantified in the field [ 3 ]. It has been well documented that K. mikimotoi exert detrimental impacts, including lethality, on a wide range of marine life, including marine fauna [ 4 , 5 ] and seaweeds [ 6 ]. Three kinds of toxins were speculated to be involved in K. mikimotoi -induced toxicity: hemolytic toxins [ 7 , 8 , 9 ], cytotoxins [ 10 , 11 ] and reactive oxygen species (ROS) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%